Evaluation of salt tolerance (NaCl) and compatibility of bael [Aegle marmelos (L.) Corr.] as rootstock of citrus trees - Toan, Nguyen Bao (Academia Journal of Biology, 2012)
Bael [Aegle marmelos (L). Corr], family Rutaceae, was grown much more in Soc Trang and Tra Vinh provinces where Khmer peoples have been living. Bael had capacity to adapt a wide range of habitat from arid to mesophytic conditions. Bael could be grown in many types of soils. It was hypothesized that Bael was able to tolerate salinity (NaCl) or not. Up to now, any articles in relation with this problem had not yet found. And because of family Rutaceae, it was supposed that Bael was used as rootstock in graft with Citrus trees, also mentioned. This research aimed to evaluate salt tolerance and compatibility of Bael as rootstock of Citrus trees. Research based on experiments in nutrient solutions supplemented salt (NaCl) at different concentrations. Grafting compatibility was evaluated through combination of Bael rootstock and scions as Citrus maxima, Citrus nobilis, Citrus sinensis and Citrus reticulate. Preliminary evaluation on fruit quality of Bael rootstock and Citrus Maxima Nam Roi also carried out. Research results showed that Bael [Aegle marmelos (L.) Corr.] was able to tolerate salinity up to 2 g/l NaCl in nutrient solutions and good compatibility in grafting among Bael rootstock and scions Citrus maxima, Citrus nobilis, Citrus sinensis and Citrus reticulate. Preliminary evaluation of fruit quality showed that fruit quality had no change when grafting between Bael rootstock and Citrus maxima Nam Roi many problems needed to be studied more before applying in the field.